1991
DOI: 10.1007/bf00232039
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic factors elicit sesquiterpenoid phytoalexin production but not alkaloid production in transformed root cultures of Datura stramonium

Abstract: The treatment of root cultures of Datura stramonium with copper and cadmium salts at external concentrations of approximately 1mM has been found to induce the rapid accumulation of high levels of sesquiterpenoid defensive compounds, notably lubimin and 3-hydroxylubimin. These compounds were undetectable in unelicited cultures. No net change was seen in the alkaloid content of the system following treatment with Cu(2+) or Cd(2+), the tropane alkaloid titre apparently being insensitive to elicitation. However, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…We have shown in a previous communication (Hilton & Rhodes 1990), that packing densities of up to 70% w/v are achievable with transformed roots of D. stramonium grown in fermenters when they are continuously fed with full strength Gamborg's B5 medium. Other methods to increase secondary metabolite production have recently been investigated and include strategies for genetic manipulation to enhance the metabolic flux in the alkaloid producing pathways , and the use of elicitors to stimulate the release of products (Furze et al 1991;Flores et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown in a previous communication (Hilton & Rhodes 1990), that packing densities of up to 70% w/v are achievable with transformed roots of D. stramonium grown in fermenters when they are continuously fed with full strength Gamborg's B5 medium. Other methods to increase secondary metabolite production have recently been investigated and include strategies for genetic manipulation to enhance the metabolic flux in the alkaloid producing pathways , and the use of elicitors to stimulate the release of products (Furze et al 1991;Flores et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Such experiments originally were carried out by Rhodes et al (1986) who used XAD-4 to adsorb nicotine from the medium of a transformed root culture of Nicotiana rustica. A recent report by Shimomura et al (1991) has extended the use of this methodology Hamill et al, 1986;Parr andHamill, 1987 Parr et al, 1988;Toivonen et al, 1989Hamill et al, 1989Deno et al, 1987Mano et al, 1989Kamada et al, 1986Jung and Tepfer, 1987;Sharp andDoran, 1990 Payne et al, 1987;Christen et al, 1989;Robins et al, 1990Flores and Filner, 1985Mano et al, 1986Nabeshima et al, 1986Y onemitsu et al, 1990Trypsteen et al, 1991Toppel et al, 1987Hartmann and Toppel, 1987Hamill et al, 1986Sauerwein et al, 1991Furze et al, 1991Marchant, 1988Westcott, 1988Croes et al, 1989Flores et al, 1988Saito et al, 1990Asamizu et al, 1988Yoshikawa and Furuya, 1987Constabe1 and Towers, 1988Berlin et al, 1988Berlin et al, 1988Shimomura et al, 1991 'In this case the roots were not transformed by A. rhizogenes but growth rates comparable to those of transformed root cultures were obtained. to enable continuous production of shikonin from a transformed root culture of L. erythrorhizon.…”
Section: J Transformed Root Culturesmentioning
confidence: 94%
“…Induction of the formation of polyacetylenic phytoalexins has been achieved in transformed root cultures of Bidens sulphureus using a fungal culture filtrate as an elicitor (Flores et al, 1988) while transformed root cultures of Hyoscyamus muticus produce sesquiterpenoid phytoalexins following elicitation (Signs and Flores, 1989). Furze et al (1991) showed that elicitations of transformed roots of Datura stramonium with Cu 2 + at 1 mM induced high levels of production of the sesquiterpenoid compounds, lubimin and 3-hydroxy lubimin which were secreted into the culture medium. In contrast, the levels of tropane alkaloids such as hyoscyamine were unaffected by the elicitor treatment.…”
Section: Elicitation In Organ Culturementioning
confidence: 99%
“…In D. stramonium the addition of those ions (l mM) induced rapid accumulation of high levels oflubimin and 3-hydroxylubimin. 76 Copper has also been used to increase growth and alkaloid accumulation in H albus. 46 Another abiotic elicitor, temperature, has been used to increase the alkaloid content in D. stramonium 5 I (Escalante, Maldonado-Mendoza and Loyola-Vargas, unpublished).…”
mentioning
confidence: 99%